Eating Disorders in Islamic Law Perspective: Study of Anorexia, Bulimia and Binge Eating among Muslims - Selian, Sri Nurhayati; Barmawi; Fanny Rizkiyani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2024)
This study examines the phenomenon of eating disorders, specifically anorexia, and bulimia, from an Islamic legal perspective with two main objectives: first, to identify awareness, familiarity, and experience of eating disorders among Muslims; second, to obtain an interpretation of Islamic law on eating disorders; The research method is qualitative with case study approach, involving six key informants consisting of one patient of anorexia nervosa, one patient of bulimia nervosa, and four patients of binge eating. The results show that awareness of eating disorders among Muslims is still limited, with many individuals and families not fully understanding the medical and psychological nature of these conditions. From an Islamic legal perspective, eating disorders are understood as conditions that require serious attention, in accordance with the principle of maqāṣid syarī’ah which emphasizes the importance of maintaining physical and mental health. However, there is still a lack of specific Islamic legal guidance related to eating disorders. The role of family and religious leaders is very important in providing support but still needs to be improved to reduce stigma and facilitate treatment. In conclusion, eating disorders require a holistic approach, combining professional help, family support, and a faith-based approach to improve the well-being of patients. This study opens up opportunities for further studies involving cross-disciplinary perspectives and focusing on the development of Islamic guidelines related to eating disorders.